The consequences of illicit drug use. Estimation, methods and challenges - Frusinoiu, Paula Ștefania; Bănacu, Cristian Silviu (Technium Social Sciences Journal, 2022)
Recognised as a contributor to the global burden of disease, drug use has been a source of continuous concern among practitioners and policy makers and a field for methodological debate among researchers. The consequences of substance use have always challenged the healthcare, social care, law enforcement and the legal system. This paper explores several methods used in estimating the costs and impact attributable to the use of illicit drugs with the aim of getting a broad understanding of the current research and the use thereof by practitioners and policy. The desk review behind this paper includes government reports, analyses and publications of relevant bodies, research done by various authors and organisations, academic investigations and findings from literature review. The case study includes an estimation of the burden of overdose deaths measured in years of life lost (YLL) and explores possible shortcomings that represent a challenge for research.